2005
DOI: 10.1080/1465980512351344101
|View full text |Cite
|
Sign up to set email alerts
|

Perceived availability of substances, substance use and substance‐related problems: a cross national study among French and Dutch adolescents

Abstract: Aim. A cross-national comparison of perceived availability of alcoholic beverages and cannabis, and of the influence of availability on consumption of and problems due to alcohol and cannabis. Method. National surveys of school-going adolescents (14-18 years) in France and the Netherlands were used. The questionnaire was comparable for all measures used in this study. We distinguished between problems with peers, with socializing agents and adverse events (e.g. fights). Cross-tabulations and logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
0
9
1
1
Order By: Relevance
“…These may suggest people who think alcohol is more available for children and adolescents are more likely to develop an alcohol use disorder and drink more but not more frequently. Our results differ slightly from results from previous studies, which showed that the perceived alcohol availability for children and adolescents is related to both alcohol use quantity, and frequency (Ahlström and Huntanen, 2007; Knibbe et al, 2005; Smart, 1977). The association between high AUDIT scores in adulthood and perceived alcohol availability for children also signified their associations with the early onset of drinking.…”
Section: Discussioncontrasting
confidence: 99%
“…These may suggest people who think alcohol is more available for children and adolescents are more likely to develop an alcohol use disorder and drink more but not more frequently. Our results differ slightly from results from previous studies, which showed that the perceived alcohol availability for children and adolescents is related to both alcohol use quantity, and frequency (Ahlström and Huntanen, 2007; Knibbe et al, 2005; Smart, 1977). The association between high AUDIT scores in adulthood and perceived alcohol availability for children also signified their associations with the early onset of drinking.…”
Section: Discussioncontrasting
confidence: 99%
“…La relación entre facilidad del suministro e intensidad del consumo ha sido habitualmente considerada dentro de la investigación sobre consumo de alcohol juvenil (Knibbe et al, 2005;Laespada y Elzo, 2007a), señalándose que la disponibilidad social de una sustancia tiene una especial incidencia en el inicio del consumo, incluso desde la preadolescencia (Komro et al, 1998). De hecho, son numerosos los autores que se refieren a que las medidas de control sobre el acceso, tales como retrasar la edad legal de dispensación o incrementar los precios de las bebidas en las tiendas, han demostrado reducir los niveles de consumo alcohólico entre los adolescentes (Anderson y Baumberg, 2006;Babor et al, 2003;Chisholm, Rehm, Van Ommeren y Monteiro, 2004;Kendel, 1996).…”
Section: El Contexto Social Cultural Y Mediáticounclassified
“…From a global perspective, the prevalence of illicit drugs seems to be higher in more developed countries (Degenhardt & Hall, 2012). In most of these countries, restrictions and measures targeted at decreasing the availability of psychoactive substances are considered to be particularly important in preventing substance use and its related problems among youths (Knibbe et al, 2005). As documented by international surveys (Currie et al, 2012;Hibell et al, 2012), however, Czech adolescents have the highest levels of both availability and prevalence of substance use compared to other European teenagers.…”
Section: Introductionmentioning
confidence: 99%